Development of Go-Bima media based on differentiated learning assisted by DIALOPAGU to improve understanding of concepts and motivation to learn mathematics in grade 4 elementary school - Defa, Defa; Sariyasa, Sariyasa; Suarni, Ni Ketut; Kertih, I Wayan (Edelweiss Applied Science and Technology, 2025)
Mathematics learning in elementary schools is often considered a process of memorizing discrete facts, thereby hindering conceptual understanding and decreasing students' motivation to learn. Therefore, teachers must use appropriate strategies to present lessons and encourage students to take a more active role in their own learning. This research aims to develop differentiated learning media based on DIALOPAGU (Digital, Loose Parts, and Songs) to enhance fourth-grade students' conceptual understanding and motivation for learning mathematics. The approach includes content, process, and product differentiation, aligned with students’ characteristics and needs as outlined by the Merdeka Curriculum. The study employs the 4D development model (Define, Design, Develop, and Disseminate). Data collection techniques include questionnaires, tests, and observations. The developed media is valid, practical, and potentially effective in improving student learning outcomes. The effectiveness of the Go-Bima media, based on differentiated learning assisted by DIALOPAGU, was demonstrated through MANOVA analysis, which revealed a significant difference in students' conceptual understanding and motivation between the experimental and control groups (p = 0.001 < 0.05). These findings underscore the importance of innovative learning media that accommodate student diversity.